2009
DOI: 10.2147/ndt.s5903
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological effects of antiepileptic drugs (carbamazepine versus valproate) in adult males with epilepsy

Abstract: Purpose:To evaluate the effect of antiepileptic drugs (AEDs) on cognition and behavior in adult epileptic males controlled on treatment with conventional antiepileptic medications.Methods:Cognitive, mood, behavior and personality traits were assessed in 45 epileptic patients treated with carbamazepine and/or valproate and free of seizures for ≥1 year. Thirty-four newly diagnosed or untreated patients with epilepsy and 58 matched healthy subjects were also included for comparison. A battery of psychometric test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 35 publications
(36 reference statements)
0
23
0
5
Order By: Relevance
“…Treated and untreated epileptic patients had poor performance of similar extent in behavioral functions testing (depression, aggression and neurosis). The dose of AEDs was correlated with testing scores for neurosis (r = 0.307; P = 0.040), verbal aggression (r = 0.483; P = 0.001) and nonverbal aggression (r = 0.526; P = 0.000), and duration of drug intake was correlated with scores for depression (r = 0.384; P = 0.009), psychosis (r = 0.586; P = 0.0001) and nonverbal aggression (r = 0.300; P = 0.045) [39].…”
Section: Effect Of Antiepileptic Drugsmentioning
confidence: 98%
“…Treated and untreated epileptic patients had poor performance of similar extent in behavioral functions testing (depression, aggression and neurosis). The dose of AEDs was correlated with testing scores for neurosis (r = 0.307; P = 0.040), verbal aggression (r = 0.483; P = 0.001) and nonverbal aggression (r = 0.526; P = 0.000), and duration of drug intake was correlated with scores for depression (r = 0.384; P = 0.009), psychosis (r = 0.586; P = 0.0001) and nonverbal aggression (r = 0.300; P = 0.045) [39].…”
Section: Effect Of Antiepileptic Drugsmentioning
confidence: 98%
“…A double-blind trial reported deterioration in measures of information processing speed and attention [Wesnes et al 2009]. Other studies report poorer verbal fluency in adults with partial seizures than in control subjects [Aikiä et al 2006], detrimental effects on memory [Shehata et al 2009;Forsythe et al 1991], worse arithmetic performance [Kang et al 2007] and faster motor skills after discontinuation [Duncan et al 1990]. Impaired movement time, reaction time, finger tapping rate and number cancellation were seen in one study, but these effects remitted by 1 month after treatment commencement [Larkin et al 1992].…”
Section: Phenytoinmentioning
confidence: 99%
“…20 Longer duration of intake, poly-therapy and higher doses are believed to be the main causative factors having impact on cognitive function. 15,20,21 Usual adult daily dose of carbamazepine is 600-1800 mg and target range of plasma concentration is 4-12 µg/ml. 3 …”
Section: Carbamazepinementioning
confidence: 99%